G248(P) Appreciation of Clinical Excellence (ACE): A Positive Feedback Tool. (24th May 2017) - Leemon, D; Anandarajan, M
Abstract : Aims: Traditionally patient safety has focussed on learning from errors. A more positive alternative is to highlight what is done well by individuals and adopt this behaviour as a team to increase the standard of care. The 4 objectives of this project are: 1) To nurture a culture of positive feedback. 2) To create a feedback tool to complement appraisal/revalidation. 3) To improve staff morale. 4) To identify areas for improvement through analysis of feedback. Methods: A simple postcard template was created with 3 questions: 1) Who achieved excellence? 2) What did they do that was excellent? 3) What could we do to develop excellence in this area? The postcards are readily available to all staff of all disciplines on the ward. They are deposited in a purpose made postbox. A champion for the project is identified and will check for reports at agreed intervals. A certificate is presented to the nominees. The initial measurements are staff morale by way of a staff morale questionnaire and staff uptake of the initiative by way of number of reports. We aim to analyse trends and categories and use appreciative inquiry to investigate the most important reports. With time we hope to identify areas of focus for improvement and provide constructive feedback for all staff as part of their continuing professional development. Results: 48% of staff completed a staff morale questionnaire prior to starting the project pilot in NICU. The majority of people agreed with 4/6 of the statements but most people disagreed with the statement 'I receive feedback on how I am performing in my job' and neither agreed or disagreed with 'My team inspires me to do my best work'. 6 ACE cards were completed during the 6 day pilot and certificates were created for each nominee. There were some positive verbal testimonials during the pilot. Conclusion: People have had a positive reaction toward the project. Next steps will involve rolling out the pilot to our general paediatric and outpatient departments. We are currently identifying champions in paediatric departments regionally and if this is successful we aim to extend the project to other specialities.